Mechanisms of salt tolerance in habanero pepper plants (Capsicum chinense Jacq.): Proline accumulation, ions dynamics and sodium root-shoot partition and compartmentation - Bojórquez-Quintal, Emanuel; Velarde-Buendía, Ana; Ku-González, Ángela; Carillo-Pech, Mildred; Ortega-Camacho, Daniela; Echevarría-Machado, Ileana; Pottosin, Igor; Martínez-Estévez, Manuel (Frontiers in Plant Science, 2014)
Despite its economic relevance, little is known about salt tolerance mechanisms in pepper plants. To address this question, we compared differences in responses to NaCl in two Capsicum chinense varieties: Rex (tolerant) and Chichen-Itza (sensitive). Under salt stress (150 mM NaCl over 7 days) roots of Rex variety accumulated 50 times more compatible solutes such as proline compared to Chichen-Itza. Mineral analysis indicated that Na+ is restricted to roots by preventing its transport to leaves. Fluorescence analysis suggested an efficient Na+ compartmentalization in vacuole-like structures and in small intracellular compartments in roots of Rex variety. At the same time, Na+ in Chichen-Itza plants was compartmentalized in the apoplast, suggesting substantial Na+ extrusion. Rex variety was found to retain more K+ in its roots under salt stress according to a mineral analysis and microelectrode ion flux estimation (MIFE). Vanadate-sensitive H+ efflux was higher in Chichen-Itza variety plants, suggesting a higher activity of the plasma membrane H+-ATPase, which fuels the extrusion of Na+, and, possibly, also the re-uptake of K+. Our results suggest a combination of stress tolerance mechanisms, in order to alleviate the salt-induced injury. Furthermore, Na+ extrusion to apoplast does not appear to be an efficient strategy for salt tolerance in pepper plants.